Metode MFEP Dalam Meningkatkan Kualitas Penentuan Rekomendasi Ekstrakurikuler - Iqbal Kamil Siregar; Muhammad Iqbal (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
One of the developments in information technology in this era of the millennial generation is a Decision Support System. This system was built with the aim of accelerating decision making and shortening time, it would take a long time if calculated/processed manually. This study aims to develop an existing system to provide efficiency and accuracy for students to provide extracurricular recommendations at the Aras Kabu Tanjungbalai Education Foundation School. The criteria and weight of the criteria that will be used as a reference in making decisions regarding these extracurricular recommendations include Interests, Talents, Achievements, Knowledge and Creativity. Then do the calculations using theMFEP method. This study found that voice guided extracurricular options were more dominant than scouts, sports and the arts.Keywords— Profile Matching, DSS, Recommendations, Extracurricular, Talent Interests.